STUDI LETERATUR : PARIWISATA SEBAGAI ILMU PENGETAHUAN,DISIPLIN ILMU ATAU KAJIAN - Yukiko Hiro Mantu (Sekolah Tinggi Pariwisata Mataram, 2020)
In the tourism literature there are differences of opinion among academics in conducting research to argue whether tourism is a scientific discipline, study or academic community. These three things are often misplaced depending on the author, the context and the author's academic’s background. This paper identifies the position of tourism in academia. These three ideas use as a tool to lead discussion. It also guides the ideas of tourism experts and Kuhn's ideas on what constitutes a scientific discipline. The discussion results is a debate of “what is the true